Музейні сувеніри як поліаспектне явище - Курдина, Юлія; Kurdyna, Yuliia (Видавництво Львівської політехніки, 2020)
У статті зроблено спробу проаналізувати музейний сувенір як багатоаспектне явище. З одного боку, сувеніри є можливістю додаткового прибутку завдяки бажанню туристів (відвідувачів) отримати матеріальний спогад про відвідане місце, з іншого – це хороший інструмент для створення та реклами власного бренду; зрештою, музейні сувеніри пов’язані із культурним туризмом. Беручи до уваги досвід інших країн, запропоновано кілька кейс-практик, які найдієвіші для виготовлення популярного асортименту музейних сувенірів.

The article attempts to analyse a museum souvenir as a multifaceted phenomenon. On the one hand, souvenirs are a possibility to earn additional profit out of the desire of tourists (visitors) to receive a material reminder of places they visited, and on the other hand, they are a good tool to create and promote own brand, after all, museum souvenirs are connected with cultural tourism. Taking into consideration that purchases are an important part of tourist activity, museums should use such activity for their own benefit for the purpose of improving competitiveness. Memories, which souvenirs carry, and usability of souvenirs play an important role. In a consumer society, the things people buy are associated with the places where they were bought. At that, historical and cultural peculiarities of those places fade into the background. Certainly, it has a negative impact on the memories of the museum in general, however, even a small mention of the place visited can provide an extra publicity to it. It should be always taken into account that souvenirs, due to their specific nature, are not common goods. They are a combination of spirit and traditions of a particular place, aspiration of tourists for lasting memories and desire of local people to preserve their culture and heritage in small tokens of remembrance. In view of the experience of other countries, a few case methods, being the most efficient in defining a popular range of museum souvenirs, can be suggested. These include visualization and replica of original source, recreation of aging effect (for example, applying patina) and reinterpretation of original function or redesign of content into a modern form.
A museum souvenir as a multifaceted phenomenon
Keywords: музей; сувеніри; брендинг; культурний туризм; museum; souvenirs; branding; cultural tourism; 338.483.12; 069; 338.487; 659.1